2012
DOI: 10.4236/ojog.2012.22027
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cervical cancer screening program in a slum setting using visual inspection with acetic acid: Analysis of feasibility and cost

Abstract: Objective: In Bangladesh, cervical cancer is the second most common cause of cancer deaths in women. Annually, over 50 million women are at risk for cervical cancer, with 17,686 cases diagnosed and 10,362 deaths each year. Visual inspection with acetic acid (VIA) is a well validated tool in low resource areas for identifying cervical lesions. In this pilot study, AK Khan Health Care Trust (AKKHCT), in collaboration with oncologists at Massachusetts General Hospital (LB, BD, AG), launched a VIA cervical cancer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
3
20
1
Order By: Relevance
“…The prevalence of VIA positive at the study clinic (12.9 %) was similar to study finding from central Ethiopia among PLWHA’s (11 %) [ 9 ] but lower than study finding from southern Ethiopia among PLWHA’s (22.1 %) [ 10 ]. It was also similar to study finding from Madagascar (11.3 %) [ 11 ], Malawi (12.4 %) [ 11 ], Latin America (12 %) [ 12 ] and Thailand (13.3 %) [ 13 ] though it is lower than study findings from Nigeria (16 %) [ 14 ], Sudan (16 %) [ 15 ] and Bangladesh (18 %) [ 16 ]. However, it is higher than study findings from Uganda (7.8 %) [ 11 ] and Tanzania (9.7 %) [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of VIA positive at the study clinic (12.9 %) was similar to study finding from central Ethiopia among PLWHA’s (11 %) [ 9 ] but lower than study finding from southern Ethiopia among PLWHA’s (22.1 %) [ 10 ]. It was also similar to study finding from Madagascar (11.3 %) [ 11 ], Malawi (12.4 %) [ 11 ], Latin America (12 %) [ 12 ] and Thailand (13.3 %) [ 13 ] though it is lower than study findings from Nigeria (16 %) [ 14 ], Sudan (16 %) [ 15 ] and Bangladesh (18 %) [ 16 ]. However, it is higher than study findings from Uganda (7.8 %) [ 11 ] and Tanzania (9.7 %) [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…There are 17,686 diagnosed cases and 10,362 deaths per year in Bangladesh [3]. For cervical cancer screening, in 2017, it was found that the crude incidence rate of cervical cancer was 12.4 per 100,000 women [4].…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis of eleven African and Indian cohort and cluster randomized trials of VIA compared to colposcopy and biopsies, VIA had a sensitivity of 79% and a specificity of 85% for the detection of CIN2 or greater [10]. A strong advantage of this technique is that it can be taught to community workers [11]. VIA can be used either as a triage to more complex screening protocols of colposcopy and biopsy or in a see-and-treat protocol [12].…”
Section: Discussionmentioning
confidence: 99%